Improving students' literacy skills through PBL model and interactive media canva class v theme II clean air for health at Pelita Private Elementary School - Ahmad Landong; Sukmawarti; Ika Nurjannah; Syilvia Cahyani Rambe; Azzahara Azzahara (Institute of Computer Science (IOCS), 2023)
Pelita Private Elementary School fifth graders were studied. Pelita Private Elementary School has 30 fifth graders—14 boys and 16 girls. Students' reading, writing, and interest in reading suffer from the teacher's boring and versatile materials. In class, students don't understand literacy. Pelita Tanjung Morawa Private Elementary School's fifth-grade primary connection test and author's homeroom teacher interviews determined Cycle I's difficulty. This study examined students' reading skills. The researcher tested students' reading skills before cycle 1. Grade 5 literacy tests average 15%. VA students excelled. Low comprehension. This initial literacy test will help create activities and learning scenarios. Canva's interactive media improves student subject matter literacy in Cycle I. Air quality. Students' reading abilities were assessed using Canva's powerpoints. Health requires clean water. Student disinterest in reading invalidates this study. Before cycle 1, the researcher assessed students' primary reading skills. Fifth-grade researchers read 15%. Grade 5 A students have low comprehension. Canva's interactive media creates learning scenarios and activities from this initial literacy assessment. Some cycle II initiatives improved performance. Pelita Private Elementary School fifth graders used tests and questionnaires in lesson II in 2022/2023. 30% were middle class and 61.65% lower class. Pelita Private Elementary School 5th graders understood exam results with 61.65% very good, 30.15% good, 8.2% fair, and 0% poor. Students' reading comprehension is reading interest. 57.2 percent of students like reading and understand. Researchers found that Canva's attractive interactive media increased students' reading interest. Canva's interactive media improves students' reading and writing.